Associations between Chinese Visceral Adiposity Index and the Risk of Metabolic Dysfunction-associated Steatotic Liver Disease and Liver Fibrosis: A Large Cross-sectional Study - Hui Liu; Mingming Deng; Gang Luo; Jie Chen (Iranian Journal of Medical Sciences)
Background: The associations between Chinese visceral adiposity index (CVAI) and non-alcoholic fatty liver disease (NAFLD) or hepatic fibrosis in Westerners are not obvious. Furthermore, metabolic dysfunction-associated steatotic liver disease (MASLD) is the new nomenclature of NAFLD, with significantly different diagnostic criteria. The present study aimed to investigate the relationships between CVAI and MASLD or hepatic fibrosis in an American population, as well as to assess the diagnostic value of CVAI for MASLD and fibrosis.Methods: After excluding missing data on calculations of indices, diagnosis of MASLD, and covariates, 3242 participants were selected from the National Health and Nutrition Examination Survey 2017-2020. Multivariate logistic regression analyses and restricted cubic spline (RCS) were used to determine the associations between CVAI and MASLD or fibrosis. The diagnostic capacity was evaluated by the area under the receiver operating characteristic (AUROC) curve. Data were analyzed using R software (version 4.2.2). P<0.05 was considered statistically significant. Results: The risk of MASLD was increased at quartiles 2, 3, and 4 compared with quartile 1 of CVAI (OR [95% CI]=3.66 [2.44-5.63], 7.954 [5.31-12.23], and 14.84 [9.80-23.06], respectively), (P<0.001). The odds ratios (95% CI) of hepatic fibrosis risk were 1.23 [0.67, 2.30], 2.44 [1.39, 4.43], 7.46 [4.36, 13.30] for the quartiles 2, 3, and 4 compared to the lowest quartile (P<0.001). According to RCS, CVAI, MASLD, and fibrosis, all had positive relationships. CVAI had AUROCs of 0.759 and 0.771 for diagnosing MASLD and fibrosis, respectively. Conclusion: The CVAI was positively related to the risk of MASLD or liver fibrosis and could be a novel biomarker for predicting MASLD and fibrosis in the American population.